Pemberi Pakan Ikan Otomatis Berbasis IOT : Penelitian - Agrinda Aulia Lubis; Dicky Apdillah; Dinda Munifah Marpaung (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Fish farming requires proper feed management to ensure optimal fish growth and cost efficiency. However, manual feeding practices are still widely applied and often lead to several problems, such as irregular feeding schedules, inaccurate feed portions, and limited pond monitoring. This study aims to design and implement an Internet of Things–based automatic fish feeding system as a solution to improve feeding efficiency and management convenience. The research method employed an engineering and experimental approach, including hardware and software system design as well as performance testing on fish farming media. The developed system is capable of scheduling and controlling feeding duration automatically while providing remote monitoring and control features through an internet connection. The test results indicate that the system achieves feeding time accuracy with an average deviation of approximately 1–2 minutes from the scheduled time and delivers relatively consistent feed portions in each feeding cycle. In addition, the system can transmit operational status data in real time, although performance is influenced by network stability. Overall, the IoT-based automatic fish feeding system demonstrates potential to enhance feed efficiency and support modern and sustainable fish farming management.